Analisis tujuan amr berkaitan makanan halal dalam surah al-Baqarah: Analysis of the purpose of amr in the context of halal food in surah al-Baqarah - Rifain, Syakirah Bt Rifa'in@Mohd; Pa, Mat Taib (al-Irsyad: Journal of Islamic and Contemporary Issues, 2020)
Do all the verses of amr have haqīqī and majāzī meanings? This study discusses the purpose of amr in surah al-Baqarah. The objective of this study is to identify the form and purpose of amr in the context of halal food in surah al-Baqarah. This is a qualitative study that uses Kuckartz (2014) text analysis techniques based on sentences and uses interpretations carried out by past and modern scholars. The author uses the ‘Abbās Theory (1997). The findings of the study found five verses about halal food in surah al-Baqarah which uses fi‘l amr. There are three purposes of amr which are wajib, ibāḥat and al-qudrat. The purpose of amr that is regularly used is ibāḥat five times, followed by wajib four times, and al-qudrat only once. In conclusion, it clearly shows that the verses of amr in the context of halal food possess the meaning of haqīqī and majāzī in surah al-Baqarah.